Use and exchange of genetic resources of emerging species for aquaculture and other purposes - Thuy T. T. Nguyen; Michael A. Rimmer; Sena S. De Silva (Blackwell Publishing Asia Pty Ltd, 2025)
From a genetic resources viewpoint, emerging aquaculture species and species groups are examined mainly in terms of food use. In addition, we include species that are becoming increasingly important for biodiversity conservation and related ecotourism aspects. Together with ornamental fish species, we argue that these species are facing increasing vulnerability and warrant attention. Our intention is to raise awareness of the potential for increasing production and revenues from emerging species ⁄ species groups with an emphasis on an underlying link to biodiversity conservation and ecosystem preservation, and how this information will inform policy on access to the genetic resources and the sharing of benefits derived from their use. For food purposes, the fastest growing aquaculture sector is mariculture, and within this sector groupers and wrasses are considered to be the most important because they cater to the relatively lucrative live food fish restaurant trade (LFFRT), which is rapidly expanding in selected South-East Asian countries. In the Asian region, ecotourism is an emerging sector and a prominent fish group for this purpose is considered to be mahseer. A number of mahseer species are culturally and commercially important and are often seen as a group of indigenous species that are suitable for aquaculture. This review summarizes much of the limited information related to the patterns of use and exchange of genetic resources on emerging aquatic species ⁄ species groups, with particular reference to Asia.